Efficacy of tiapride in the treatment of psychiatric disorders: A systematic review. (21st March 2022) - Zangani, Caroline; Giordano, Barbara; Stein, Hans‐Christian; Bonora, Stefano; Ostinelli, Edoardo Giuseppe; D'Agostino, Armando
Abstract: Background: Tiapride is an atypical antipsychotic used to treat alcohol withdrawal, aggressiveness and agitation, headache, dyskinesias, tic and Tourette's disorder. More recently, it has been proposed for the treatment of delirium and agitation in hospitalised patients with COVID‐19. Although its safety profile makes it suitable for use in vulnerable populations, the use of tiapride for psychiatric disorders is limited. This work aims to systematically review the available evidence on the efficacy and tolerability of tiapride in individuals with a psychiatric disorder. Methods: We searched PubMed, Embase, PsycINFO, GreyLit, OpenGrey, and ProQuest up to March 2020 for randomised controlled trials focussing on the use of tiapride in the treatment of individuals with a psychiatric disorder (e.g., mood disorder, schizophrenia spectrum, substance use disorder). The Risk of Bias 2 was performed for the quality assessment of the included studies. Results: We identified 579 records. Of them, six studies (published between 1982 and 2010) were included in the review. Four studies referred to alcohol withdrawal, and two to the management of agitation in elderly patients with dementia. None of the studies reported significant differences between tiapride and other active comparators in terms of efficacy and tolerability. The overall risk of bias was moderate to high. Conclusion: Tiapride may be considered as a relatively safe treatment option for selected patients with alcohol withdrawal or agitation in dementia. However, solid evidence of its efficacy in the scientific literature is lacking. High‐quality trials remain necessary to fully sustain its use in clinical practice.